Co-PP/EPDM Blend Optimization Using D-Optimal Design for Medical Applications. Issue 2 (22nd January 2017) - Balaji, Anand Bellam; Khalid, Mohammad; Ratnam, Chantara Thevy; Michael, Feven Mattews; Walvekar, Rashmi
ABSTRACT: This work focuses on the optimization and identification of blend with balanced mechanical properties of Co-PP/EPDM. The blending factors include time, temperature, screw speed, and blend ratio. Tensile strength and elongation at break were studied as the two responses. D-Optimal model was used to fit the regression line, which was validated using analysis of variance and "lack of fit" test. An average error of 10% (for tensile strength) and 3.2% (for elongation at break) was observed between the actual and predicted values. Further, the thermal stability, dynamic mechanical analysis, and phase morphology of the optimized blend were also investigated. GRAPHICAL ABSTRACT: